Fermentação de diferentes méis, melado de cana e xarope de glicose: acompanhamento do perfil químico, análise do teor de fenólicos e atividade antioxidante. - Niemes, João Paulo (2018)
The present study verified the influence of different fermentation conditions (time, temperature and strain) on the preparation of mead, cane syrup and corn syrup fermented. The total phenolic content was preserved (except for cane syrup fermented) and the increase of antioxidant activity in the fermented in relation to raw materials (except for cane syrup samples) was observed, and this event could be related to the increase of the concentration of DDMP (3,5-dihydroxy-6-methyl-2,3-dihydropyran-4-one). The fermented pH values did not change significantly. However, the values of acidity increased, which is related to the metabolism of the yeast, that trough formation and release of acetic acid results in this elevation. The determination of mineral profile shows that in order to have an adequate fermentation performance, mineral supplementation of the must is necessary, especially in relation to the magnesium and zinc contents, which participate in a series of enzymatic reactions. The values of alcohol content obtained were in the range of 10.2 to 11.7oGL, being these values for the temperatures of 28oC, associating the highest fermentation efficiencies (79.60 to 96.99%). Under non-ideal conditions, that is to use a high fermentation strain at a temperature of 10°C, the fermentation efficiency was low, ranging from 34.01 to 48.32% (4.0 to 5.8°C), showing that the yeast experienced deceleration of the anaerobic pathway through osmotic stress. As an exception to this behavior is the BB10L sample, which presented a value of 5.7 ± 0.6 oGL. This low efficiency may be related to inhibitory processes caused by the composition of mellipona Jataí honey, being zinc deficiency one of the possible responsible for this behavior. However, as the acidity of this sample was at 20.7 ± 1.5 mEq L-1 this condition becomes interesting for the production of a softer mead. A chromatographic direct method using HPLC/UV for quantification of 5-hydroxy-2-methyfurfuraldehyde (HMF) content in different fermented beverages (mead, cane syrup fermented and corn syrup fermented) was developed and in House validated using sophisticated statistical tools at the first time in this work. HMF separation was carried out with isocratic elution of a mobile phase comprising water (with 0.5% formic acid) and acetonitrile (90:10, v v-1), at 30oC, flow rate of 1.0 mL min-1, injection volume of 5.0 μL and detection at 285 nm. Validation study demonstrate that the developed method has good performance, presenting low limits (LOD and LOQ of 0.16 and 0.53 mg L-1, respectively), good accuracy (recovery rates between 82.3 and 95.9%) and precision (RSD values between 3.87 and 8.84% and Horrat values between 0.43 and 0.76). Adequate selectivity and linearity estimates were also observed (R2 > 99.5%). Fermented beverages from honey, cane syrup and corn syrup presented HMF contents lower than starting foods used in fermentation. Besides this, results demonstrated that fermentation conditions are a key parameter for obtaining fermented beverages with low levels of this contaminant, and that the fermentation can be a strategy for mitigation of HMF in foods such honey, cane syrup and corn syrup.